Wireless ECG Circuit on Flexible Material: A Preliminary Study - Sahar, N. S.; Abdul-Kadir, N. A.; Chan, W. H.; Su, E. L. M.; Che Harun, F. K. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Flexible printed circuit is rapidly developing in the electronics industry. However, the circuit substrate of flexible materials limited due to its temperature limitation characteristics. In this study, two flexible materials were tested: a silicon rubber and a thermoplastic polyurethane (TPU). The effectiveness of the fabrication process on both materials was compared using a vinyl cutter. Results showed that the TPU material is better for the fabrication process due to the roughness of its surface which is higher than silicon rubber that makes the adhesion of the copper tape stronger on the surface.